Determinants of Dividend Policy with Good Corporate Governance as a Moderator: Evidence from LQ45 Companies on the Indonesia Stock Exchange - Suhandi; Tri Kunawangsih Purnamaningrum; Pardomuan Sihombing (PT. INOVASI TEKNOLOGI KOMPUTER, 2025)
The goal of this study was to examine LQ45 businesses' dividend policies on the Indonesia Stock Exchange by dissecting their dividend policy drivers and controlling variables using excellent corporate governance as a moderator. Participants in the research were companies that were included in the LQ45 index for the years 2019 and 2023. As part of a causal research strategy, hypothesis testing was used. The sample was determined using a purposeful sampling technique, which resulted in 25 sample businesses. In order to analyze the data, panel data regression was used. This statistical program was constructed using Eviews version 13.0. Results showed that dividend policy is affected by profitability, interest rates, and excellent corporate governance in a favorable way, and by leverage and free cash flow in a negative one. There was also no correlation between company size and dividend policy. One interesting finding is that effective corporate governance acts as a moderator, enhancing the influence of free cash flow on dividend policy while reducing the impacts of profitability, debt, and firm size. Good corporate governance did nothing to reduce the correlation between dividend policy and interest rates.